Correlation between Students’ Self-Efficacy and Teachers’ Educational Leadership Style in Iranian Midwifery Students - Sohrabi, Zohreh (Glob J Health Sci, 2016)
BACKGROUND: Self-efficacy is believe in and feeling of ability to complete work. One of these factors is educational teachers’ role. This study aimed to determine relationship between teachers’ leadership style and students’ self-efficacy in midwifery students. METHOD: This Study is a cross sectional correlation study. Sampling was conducted in midwifery students in Bachelor Science degree in 2013. Data collection tools were multi leadership questionnaire and self-efficacy clinical performance. After explaining the goals of study, 97 students completed the questionnaire. Scoring the questionnaire was based on a Liker’s scale (0-5). Data were analyzed by SPSS 16. Correlation coefficient test was adopted to investigate the relationship and p value was considered 0.05. RESULT: Mean of self-efficacy scores were 116.12 (24.66.). In 53.3% of the cases, self-efficacy was good, in 42.2% moderate and in 4.3%, it was bad. The majority of the students (88.9%) reported that their teachers had an idealized style in leadership. About 94.6% of the students with good self- efficacy believed that their teachers’ leadership style was transformational style. There was a significant correlation between self- efficacy and leadership style (p<0.05). CONCLUSIONS: Results showed that transformational style is appropriate for midwifery teachers.